Peran Media Sosial dalam Membangun Komunitas Pecinta Kopi: Peluang dan Tantangan Bagi Coffeepreneur - Rian Andriani; Yen Efawati; Ade Mubarok; Tresna Budiarti (Carmin: Journal of Community Service, 2025)
This article discusses the development of MSME potential in Legok Harendong Village, Bandung Regency, through the use of social media and digital distribution. This area is famous for its honey orange commodities and Arabica and Robusta coffee, which thrive due to the hilly geographical conditions and the dominance of the community as farmers. However, limited infrastructure, digital literacy, and marketing strategies are the main challenges for MSMEs in developing their businesses. This community service activity aims to enhance the capacity of MSME actors, particularly Elgeha coffee entrepreneurs, through digital marketing socialization, social media content training (including Instagram, Facebook, and WhatsApp), and product catalog creation on e-commerce platforms. The approach used is Participatory Action Research (PAR), which is a collaborative approach that actively involves MSME actors in the process of identifying problems, training, and mentoring in digital marketing based on social media. The results show an increase in business knowledge and ability in using digital media for promotion and distribution. In addition, the formation of a coffee lover community is bold, which expands networks and market potential. This program shows that digital transformation at the village MSME level can be an effective strategy in strengthening competitiveness and accelerating local economic growth sustainably.